THE CORRELATION OF ANEMIA AND HEPCIDIN SERUM LEVELS IN REGULAR HEMODIALYSIS PATIENTS WITH CHRONIC HEPATITIS C IN HAJI ADAM MALIK HOSPITAL MEDAN - Wingsar Indrawanto; Adi Koesoema Aman; Alwi Thamrin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
End-Stage Renal Disease (ESRD) patients who undergo hemodialysis therapy are high-risk populations infected by the hepatitis C virus. Some studies have reported that hepcidin levels were decreased in patients with chronic hepatitis C. Hepcidin serum concentrations were also reported to increase in patients with renal failure in the line with increased severity of renal failure, which can cause the accumulation of hepcidin culminating in anemia due to iron deficiency. This study was to analyze the correlation of anemia and hepcidin serum levels in ESRD patients who underwent regular hemodialysis with chronic hepatitis C. This was an analytical observational study with cross-sectional design, conducted on 24 ESRD patients with chronic hepatitis C and 24 patients with ESRD without hepatitis who were undergoing regular hemodialysis therapy in the Adam Malik Hospital, Medan during July – September 2016. All study subjects were examined for full blood count and hepcidin serum levels. The result of the iron status was recorded from the patient’s medical record. In this study, the mean hemoglobin was 8.15±1.44 g/dL, mean hematocrit 25.42±4.53%, median hepcidin levels 29.75 (4.92-359.49) in the ESRD patients with chronic hepatitis C and mean hemoglobin 8.21±1.50 g/dL, mean hematocrit 25.25±4.37%, median hepcidin levels 30.33 (11.65-141.53) in the ESRD patients without hepatitis. The Spearman’s rho test showed a positive correlation that was significant between hepcidin and hemoglobin (r = 0.439, p=0.032), hepcidin and hematocrit (r = 0.021; p=0.024) in ESRD patients with chronic hepatitis C. This study showed a positive correlation between anemia and hepcidin serum levels in ESRD patients with chronic hepatitis C who underwent regular hemodialysis.